Safety culture maturity at work in a plastic packaging factory - Silva, Mygre Lopes da; Borba, Vinícius dos Santos; Pauletti, Iana Suertegaray; Silva, Rodrigo Abbade da (Revista de Administração da UFSM, 2023)
Purpose: This study aims at analyzing the stage of the safety culture maturity at work in the logistics sector of a flexible plastic packaging company located in the South of Minas Gerais. This research aims to answer the following question: what is the stage of the safety culture maturity at work in Alfa’s organization unit? Design/methodology/approach: The research is characterized as descriptive and quantitative. The method used is the survey, based on a questionnaire developed by Gonçalves Filho, Andrade and Marinho (2011). The study sample consisted of 32 operational employees and three managers responsible for occupational safety in the sector. Data were analyzed using descriptive statistics, based on relative frequency. Findings: It was observed that the information, communication, and commitment factors are in the constructive stage, in the highest maturity level of the safety culture at work. The other factors are in the proactive stage, transitory to the constructive stage. There is an efficient management system for work security and an effective workplace safety culture. Originality/value: This research sought to contribute to the discussion on the maturity of the safety culture at work, due to the scarcity of research in the plastics industrial sector. The research analyzes the organization's logistics sector, the sector that has the highest incidence of accidents, allowing comparisons between the perception of the shop floor and the management.